A novel system for embryo-larval toxicity testing of pelagic fish: Applications for impact assessment of Deepwater Horizon crude oil. (November 2016) - Stieglitz, John D.; Mager, Edward M.; Hoenig, Ronald H.; Alloy, Matthew; Esbaugh, Andrew J.; Bodinier, Charlotte; Benetti, Daniel D.; Roberts, Aaron P.; Grosell, Martin
Abstract: Key differences in the developmental process of pelagic fish embryos, in comparison to embryos of standard test fish species, present challenges to obtaining sufficient control survival needed to successfully perform traditional toxicity testing bioassays. Many of these challenges relate to the change in buoyancy, from positive to negative, of pelagic fish embryos that occurs just prior to hatch. A novel exposure system, the pelagic embryo-larval exposure chamber (PELEC), has been developed to conduct successful bioassays on the early life stages (ELSs; embryos/larvae) of pelagic fish. Using this unique recirculating upwelling system, it was possible to significantly improve control survival in pelagic fish ELS bioassays compared to commonly used static exposure methods. Results demonstrate that control performance of mahi-mahi ( Coryphaena hippurus ) embryos in the PELEC system, measured as percent survival after 96-hrs, significantly outperformed agitated static exposure and static exposure systems. Similar significant improvements in 72-hr control survival were obtained with yellowfin tuna ( Thunnus albacares ). The PELEC system was subsequently used to test the effects of photo-induced toxicity of crude oil to mahi-mahi ELSs over the course of 96-hrs. Results indicate a greater than 9-fold increase in toxicity of Deepwater Horizon ( DWH ) crude oil during co-exposure to ambient sunlight compared to filtered ambient sunlight, revealing the importance of including natural sunlight in 96-hr DWH crude oil bioassays as well as the PELEC system's potential application in ecotoxicological assessments. Graphical abstract: Images and diagrams are from the corresponding author and shapes were created by the corresponding author using Microsoft PowerPoint. Highlights: A novel exposure system for fish ELS toxicity testing (the PELEC) is reported. The method improves ELS toxicity testing of high-value pelagic fish species. Testing results indicate that mahi-mahi embryos are highly sensitive to PAHs. The PELEC also allows for testing of photo-induced crude oil toxicity. Natural sunlight co-exposure with DWH crude oil significantly increases toxicity.